The efficacy of Pj4CS (integrated project-based and 4C-scaffolding) on higher-order thinking skills - Astuti Muh Amin; Fitriyah Karmila; Muh Khalifah Mustami; Noor Hujjatusnaini; Romi Adiansyah; Atia Cahyani Putri Cando; Siti Fatimah Albaar (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The enhancement of higher-order thinking skills (HOTS) can be achieved through the implementation of active learning models. The current study aimed to examine the efficacy of the Pj4CS (Integrated Project-Based and 4C-Scaffolding) learning model on pre-service biology teachers’ HOTS. This study employed a quasi-experimental design. The independent variable in this study was the Pj4CS (Integrated Project-Based and 4C-Scaffolding) learning model, while the dependent variable was HOTS. The research sample consisted of 50 biology education students. Prior to its use, the HOTS instrument had gone through a validation process. The findings indicated that the mean post-test HOTS score in the experimental group utilizing the Pj4CS model was 81.135, whereas the mean post-test HOTS score in the control group employing the STAD model was 43.183. According to the results, it was concluded that the Pj4CS model could enhance students’ HOTS more effectively than the STAD Model. The findings also underlined the efficacy of the Pj4CS model on pre-service biology teachers’ HOTS. The Pj4CS model’s stages which comprise Critical reading; Communication for project determination; Collaborative participation; Scaffolding; Creativity exploration, were proven effective in promoting HOTS. The findings of this study may facilitate subsequent research focused on the application of learning models in the classroom to address 21st-century educational needs.